Depletion of activated macrophages with a folate receptor-beta-specific antibody improves symptoms in mouse models of rheumatoid arthritis - Hu, Yingwen; Wang, Bingbing; Shen, Jiayin; Low, Stewart A.; Putt, Karson S.; Niessen, Hans W. M.; Matteson, Eric L.; Murphy, Linda; Ruppert, Clemens; Jansen, Gerrit; Oliver, Stephen J.; Feng, Yang; et al. (Arthritis research & therapy, 2019)
Objectives Most therapies for autoimmune and inflammatory diseases either neutralize or suppress production of inflammatory cytokines produced by activated macrophages (e.g., TNFα, IL-1, IL-6, IL-17, GM-CSF). However, no approved therapies directly target this activated subset of macrophages. Methods First, we undertook to examine whether the folate receptor beta (FR-β) positive subpopulation of macrophages, which marks the inflammatory subset in animal models of rheumatoid arthritis, might constitute the prominent population of macrophages in inflamed lesions in humans. Next, we utilized anti-FR-β monoclonal antibodies capable of mediating antibody-dependent cell cytotoxicity (ADCC) to treat animal models of rheumatoid arthritis and peritonitis. Results Human tissue samples of rheumatoid arthritis, Crohn’s disease, ulcerative colitis, idiopathic pulmonary fibrosis, nonspecific interstitial pneumonia, chronic obstructive pulmonary disease, systemic lupus erythematosus, psoriasis, and scleroderma are all characterized by dramatic accumulation of macrophages that express FR-β, a protein not expressed on resting macrophages or any other healthy tissues. A monoclonal antibody to FR-β accumulates specifically in inflamed lesions of murine inflammatory disease models and successfully treats such models of rheumatoid arthritis and peritonitis. More importantly, elimination of FR-β-positive macrophages upon treatment with an anti-FR-β monoclonal antibody promotes the departure of other immune cells, including T cells, B cells, neutrophils, and dendritic cells from the inflamed lesions. Conclusions These data suggest that specific elimination of FR-β-expressing macrophages may constitute a highly specific therapy for multiple autoimmune and inflammatory diseases and that a recently developed human anti-human FR-β monoclonal antibody (m909) might contribute to suppression of this subpopulation of macrophages.